Kampus Alam Tegalsari Indonesia (KATI): Integrasi Pendidikan, Konservasi, dan Pemberdayaan Masyarakat di Desa Sidodadi - Muhammad Fadhil; Nadia Safira Amalia Rahmasari; Hasanatut Thoyyibah; Fiqhan Khoirul 'Alim (Universitas Islam Internasional Darullughah Wadda'wah, 2025)
The coastal area of Sidodadi Village, Malang Regency, has experienced environmental damage in the form of annual flooding, erosion of the Penguluran River cliffs, and degradation of the mangrove ecosystem. The 2013 flood, with a water level of 3.5 meters, showed that the risk of disaster remains high. Previous independent conservation efforts have not had a significant impact, while the village's natural potential has not been optimally utilized. This study used a qualitative Participatory Action Research (PAR) approach, through five stages: problem identification, action planning, implementation, evaluation, and reflection, with the community of Sidodadi Village as active partners. The goal was to develop an integrated conservation model that integrates environmental education, community empowerment, and structured ecological action, while optimizing local potential for a sustainable economy. The research resulted in the establishment of the Tegalsari Indonesia Nature Campus (KATI) as a center for conservation education, including the establishment of a Mangrove Seed Bank, mapping of the Bajulmati River, data-based mangrove planting, and environmental education modules. Initial impacts include increased youth involvement, ecological literacy, and more coordinated and sustainable environmental management.